Analisis Patriarki Dalam Lensa Budaya Jawa Pada Film Pendek “Something Old, New, Borrowed, and Blue” - Varlina, Vivi; Rachmatullah, Muhammad Krisna (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
The short film "Something Old, New, Borrowed, and Blue" encapsulates a thought-provoking narrative about the reflection of patriarchy in Javanese culture. The film opens a window to explore the complexity of gender and power dynamics in Javanese society. This research uses a qualitative descriptive study method and Roland Barthes' semiotic approach to explore the meaning contained in the text or media in the movie. The results illustrate the impact that patriarchal values have on women in Javanese culture. Concepts such as "Something Old" emphasize the power of tradition that plays a role in maintaining gender hierarchy, while "Something New" highlights the challenges women face in the transition phase of marriage. "Borrowed" and "Blue" show the complex pressures women experience in fulfilling their roles. The film becomes a tool to deepen our understanding of patriarchy in Javanese culture, enriching our insight into the complexity of social and gender relations within it, and highlighting the struggles and strengths of women in the face of dominant cultural structures.